Organometallic syntheses - Eisch, John J.; King, R. Bruce (Academic Press, 1965)
Over 160 detailed and tested procedures for the preparation of specific organometallic compounds are given in Volume 4. Part I contains procedures for the synthesis of 76 types of transition metal organometallic compounds, and Part II procedures for the synthesis of 85 nontransition metal organometallic compounds. In both parts, the editors have sought to include procedures that give the safe, reliable synthesis of organometallic compounds that can lay some claim to significance in current chemical research. This significance may be based on various factors such as: (a) the synthesis describes the formation of an unusual or less common structural type; (b) the compound prepared is a useful intermediate in other syntheses; (c) the compound is a model reagent for investigating the mechanisms of various fundamental or industrial processes, such as the Fischer-Tropsch reaction; (d) the compound is a useful reagent in organic synthesis; and (e) the techniques employed in the synthesis of the compound are unusual and worthy of further application, such as metal-atom and electrochemical procedures. Each specific or generalized procedure is organized into the following sections: an Introduction which discusses the available procedures and the reasons guiding the choice of the one selected; a Procedure section which strives to describe the modus operandi, the safety concerns and pitfalls in the preparation; a Properties section that offers further physical and chemical data on the product and, where appropriate, indications of how the compounds can be employed in research; and a Reference section which gives both leading literature citations and supplemental comments on the procedure. Research laboratories in organometallic chemistry, organic chemistry, inorganic chemistry and molecular catalysis have in this book a rich source of information on the preparation of organometallic compounds.